2016
DOI: 10.1007/s10646-016-1649-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological evaluation of foundry sands and cosmetic sludges using new earthworm biomarkers

Abstract: The management and final disposal of industrial wastes are a matter of considerable human concern. The present study evaluates the cyto/genotoxic effects and changes of the coelomic cell formulas exerted by aqueous leachates and solid waste (SW) of two industrial residues using coelomocytes extruded from Eisenia fetida. The assayed wastes corresponded to industrial foundry and cosmetic activities. After 14 days of exposure, we obtained a group of endpoints that reflect the toxicity/genotoxicity, coelomocyte fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Widely used ecotoxicological methods include organisms from all levels of the food-chain, e.g. aquatic organisms for waste-water or leachate assessment (Quilici et al 2004), earthworms for soil contamination assessment (Quilici et al 2004;García-Gómez et al 2014a;Curieses et al 2016), snails for contaminated area assessment (Dallinger et al 2004). One of the varieties of ecotoxicity tests is based on the use of plants, these are called phytotoxicity tests.…”
Section: Introductionmentioning
confidence: 99%
“…Widely used ecotoxicological methods include organisms from all levels of the food-chain, e.g. aquatic organisms for waste-water or leachate assessment (Quilici et al 2004), earthworms for soil contamination assessment (Quilici et al 2004;García-Gómez et al 2014a;Curieses et al 2016), snails for contaminated area assessment (Dallinger et al 2004). One of the varieties of ecotoxicity tests is based on the use of plants, these are called phytotoxicity tests.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the proportion of the different cellular types of coelomocytes may be related to the health and the immune earthworm responses [23,28,35]. Thus, changes in cell proportions in the coelomic fluid of organisms exposed to different pollutants can be evaluated by means of this parameter as a reliable cytotoxic biomarker, as suggested elsewhere [15,37,38]. In agreement, it has been demonstrated that eleocyte proportions of another oligochaeta Dendrobaena veneta decreased after exposure to cadmium and copper [36].…”
Section: Introductionmentioning
confidence: 53%
“…Zhang et al [62] described different inhibition effects on the luminescent bacteria Vibrio fischeri. Curieses and co-workers [63] assessed the toxicity/genotoxicity of foundry sands on the earthworm Eisenia fetida. A comprehensive toxicological evaluation of extracts of concrete containing WFS was performed on crustacean Daphnia magna, Allium cepa (onion roots) and Eisenia fetida [64].…”
Section: Ecotoxicity Testsmentioning
confidence: 99%